COVID-19 cynomolgus macaque model reflecting human COVID-19 pathological conditions - Urano, Emiko; Okamura, Tomotaka; Ono, Chikako; Ueno, Shiori; Nagata, Satoshi; Kamada, Haruhiko; Higuchi, Mahoko; Furukawa, Mugi; Kamitani, Wataru; Matsuura, Yoshiharu; Kawaoka, Yoshihiro; Yasutomi, Yasuhiro (Proceedings of the National Academy of Sciences - PNAS, 2021)
The pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global threat to human health and life. A useful pathological animal model accurately reflecting human pathology is needed to overcome the COVID-19 crisis. In the present study, COVID-19 cynomolgus monkey models including monkeys with underlying diseases causing severe pathogenicity such as metabolic disease and elderly monkeys were examined. Cynomolgus macaques with various clinical conditions were intranasally and/or intratracheally inoculated with SARS-CoV-2. Infection with SARS-CoV-2 was found in mucosal swab samples, and a higher level and longer period of viral RNA was detected in elderly monkeys than in young monkeys. Pneumonia was confirmed in all of the monkeys by computed tomography images. When monkeys were readministrated SARS-CoV-2 at 56 d or later after initial infection all of the animals showed inflammatory responses without virus detection in swab samples. Surprisingly, in elderly monkeys reinfection showed transient severe pneumonia with increased levels of various serum cytokines and chemokines compared with those in primary infection. The results of this study indicated that the COVID-19 cynomolgus monkey model reflects the pathophysiology of humans and would be useful for elucidating the pathophysiology and developing therapeutic agents and vaccines.